2013
DOI: 10.1159/000354721
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Cutaneous Lupus Erythematosus Triggered by Radiotherapy

Abstract: Background: The origin of collagen autoimmune diseases is not fully understood. Some studies postulate a mechanism of molecular mimicry or heterologous immunity following viral infections triggering autoimmunity. Apart from infections, other exogenous factors such as visible light or X-rays have been reported to incite autoimmunity. Case Report: We report a case of histologically and serologically confirmed subacute lupus erythematosus (SCLE) following radiotherapy for breast cancer. Discussion: The close temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Radiation-induced SCLE is an uncommon presentation, with only four cases described in the literature, all of which were patients with breast cancer who had no prior history of CLE. In one 3 of the four reported cases, the eruption was confined to the radiation field, while in the others, 1,2,4 it extended beyond the field as in our case. The time of onset varied; two cases had occurrence during the radiotherapy treatment course, 1,2 one presented just after completion of the course 3 as in our case, and one had a delayed onset, presenting approximately 4 months after radiotherapy completion.…”
Section: (B)supporting
confidence: 56%
See 1 more Smart Citation
“…Radiation-induced SCLE is an uncommon presentation, with only four cases described in the literature, all of which were patients with breast cancer who had no prior history of CLE. In one 3 of the four reported cases, the eruption was confined to the radiation field, while in the others, 1,2,4 it extended beyond the field as in our case. The time of onset varied; two cases had occurrence during the radiotherapy treatment course, 1,2 one presented just after completion of the course 3 as in our case, and one had a delayed onset, presenting approximately 4 months after radiotherapy completion.…”
Section: (B)supporting
confidence: 56%
“…To our knowledge there are only two other cases reported of teriflunomide-induced pustular psoriasis in the literature, 1,2 although other cutaneous adverse effects (AEs), including development and worsening of plaque psoriasis, psoriasiform nail disease and toxic epidermal necrolysis, have also been reported. [3][4][5] A 52-year-old man with MS was treated with teriflunomide (Aubagio â ; Sanofi Genzyme, Framingham, MA, USA), a disease-modifying drug for relapseremitting disease. His medical history included MS and he had no personal or family history of psoriasis.…”
mentioning
confidence: 99%
“…There have been previous case reports of SCLE triggered by radiotherapy. 7 , 8 It was suggested that an autoimmune reaction may have been triggered locally by ionizing radiation functionally altering the immune system and breaking self-tolerance. 7 It should be noted that we cannot definitively identify radiation as the trigger of cutaneous lupus erythematosus in our patient; chemotherapy is a possible trigger as well.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that the autoimmune reaction of SLE was possibly triggered locally due to the activation of an autoantigen recognizing potential inflammation after radiation was administered the first time. 15 Another possible explanation is a previously unreported reaction with hydroxychloroquine and radiation, similar to a radiation recall seen with antineoplastics. 16 One case study also showed a patient with SLE who developed “pruritus and cutaneous reactions like rash, exanthematous pustulosis, and urticaria” after antimalarial administration.…”
Section: Discussionmentioning
confidence: 95%
“…The exact mechanism of the radiation-induced lupus flare remains uncertain. One hypothesis is that the autoimmune reaction of SLE was possibly triggered locally due to the activation of an autoantigen recognizing potential inflammation after radiation was administered the first time 15 . Another possible explanation is a previously unreported reaction with hydroxychloroquine and radiation, similar to a radiation recall seen with antineoplastics 16 .…”
Section: Discussionmentioning
confidence: 99%